Maternal and paternal overprotection of children born preterm: relations to child and parental factors - Toscano, C; Soares, I.; Baptista, J.; Moutinho, J.; Rippe, R.; Mesman, J. (Journal of Family Psychology, 2022)
The purpose of this study was to investigate the correlates of observed overprotective behaviors of mothers and fathers of preterm-born preschoolers. Participants included 85 children born prematurely (gestational age <37 weeks) and their parents, assessed when children were 12, 24, and 42 months old. Observed overprotection was measured through the standardized observation of a parent–child interaction. The examined correlates included parent-reported perception of their protective behavior, parental gender, child neonatal risk, child development, parent-reported perception of child vulnerability, parent-reported psychological distress, and family’s socioeconomic disadvantage. Results revealed that the correlation between parent-reported and observed parental overprotection was not significant for mothers and fathers. There was a significant positive association between maternal and paternal observed overprotection and no significant differences between mothers’ and fathers’ overprotection levels. Lower child developmental level and more socioeconomic disadvantage at child’s 12 months of age were significant predictors of observed overprotective behaviors. Findings suggest the importance of targeting parents of preterm-born children with socioeconomic disadvantages and whose children have a lower developmental level for providing support to both mothers and fathers in the development of more adaptive parenting strategies.